Analysis of degradation failure of poly L-lactic acid fixators used in meniscus tears - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2008)
Objectives: Biodegradable poly L-lactic acid (PLLA) fixators used in the repair of meniscal tears may cause adverse reactions inside the knee due to delayed degradation. This Study was designed to determine the reasons for late degradation of PLLA fixators. Methods: Three unused and three used meniscal PLLA fixators (BioStinger) were analyzed. The latter were removed from three patients due to persisting symptoms within six months after knee arthroscopy. Fourier transform infrared (FTIR) spectroscopy was performed and external and internal surfaces of the samples were examined by scanning electron microscopy (SEM) and C X-ray fluoroscopy (XRF). Chemical structural analyses of two samples (one from each group) were made by H-1-nuclear magnetic resonance (H-1-NMR) spectroscopy. Degradation times of two samples (one from each group) by oxidative hydrolysis in hydrogen peroxide solution were recorded. Results: Chemical structure of used and unused fixators did not differ in FTIR analysis. With increasing temperatures. unused and used fixators showed degradation with and without melt flow, respectively. In SEM analysis. inner sections of unused fixators were homogeneous. whereas those of the used ones exhibited crystals which were found to be sodium and potassium chloride salts in XRF analysis. The H-1-NMR spectrum of used and unused samples showed the normal pattern of lactic acid polymer. The unused and used fixators degraded in hydrogen peroxide solution in 10 days and 30 days, respectively. Conclusion: Both fixators had the same chemical structure in FTIR and NMR analyses. Formation of salt crystals seemed to be the most important cause of degradation failure, while changes in the physical properties of fixators were thought to be associated with delayed degradation.
Keywords: Absorbable implants; arthroscopy; biocompatible materials/adverse effects; menisci, tibial/surgery; polyesters/metabolism; prostheses and implants/adverse effects; FIXATION; FRACTURES; IMPLANTS; REPAIR; SCREWS; BONE